Optimization of Musalais wine formula based on response surface methodology - ZHU Shaolin, CHEN Qiling, WANG Chen, ZHANG Wanxueer, HE Jing, GUO Shengting, YANG Xingyuan (Zhongguo niangzao)
In this study, using Musalais wine as base wine, and medicinal and edible homology plants such as black wolfberry, Cistanche deserticola, jujube and sea buckthorn as auxiliary materials, the Musalais wine with new formula was prepared by soaking the base wine with auxiliary materials. Using total flavonoids content and sensory score as response values, the formula of Musalais wine was optimized by single factor combined with response surface tests. The basic physicochemical indexes were analyzed, and the effects of different auxiliary materials on the physicochemical indexes and sensory evaluation of Musalese wine were investigated. The results showed that the optimal formula of Musalais wine was black wolfberry 8.8 g/L, C. deserticola 8.3 g/L, jujube 10.4 g/L, sea buckthorn 4.2 g/L. The total flavonoids content in the Musalais wine with new formula reached 0.61 g/L under these optimal conditions, with a sensory score of 91, and the contents of total phenols, total flavonoids, fructose and glucose were increased by 0.45 g/L, 0.29 g/L, 5.15 g/L, 7.13 g/L, respectively. All 4 auxiliary materials could increase the malic acid, fructose and glucose contents of the wine, and the addition of jujube and C. deserticola significantly increased the lactic acid content of the wine, while the addition of sea buckthorn significantly increased the total flavonoids content of the wine. The addition of auxiliary materials enhanced the organoleptic complexity of Musalais wine, and the finished wine had a good overall performance in terms of comprehensive, appearance, aroma, taste and balance.